Akuntabilitas Pengelolaan Dan Pemanfaatan Dana Desa Dalam Meningkatkan Pembangunan Desa Di Desa Ciherang Kecamatan Gunungsari Kabupaten Serang – Banten - Efi Tajuroh Afiah; Rohayati Rohayati; Aris Trismayadi Nurizki (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study is entitled Management And Accountability Analysis Utilization of Village Funds in Increasing Village Development. This research intended to know the management and utilization of villagefunds in the village Ciherang. This study aims to determine financial management as well use of village Funds and to find out the obstacles the implementing team in carry out the process of building facilities and infrastructure funded by funds village in Ciherang Village. This research uses an analytical method with a qualitative approach. Researchers use this approach to get a picture of that overall about the process of managing and utilizing village funds in the village Ciherang Gunungsari District, Serang Regency. Data collection at do with the method of observation and interviews. The results of this study indicate that the accountability of financial management in the village of Ciherang has been carried out properly and can be accounted for both in physical form and financial reports, but there are still obstacles experienced by the village implementation team in carrying out the construction of facilities and infrastructure funded by village funds, namely the lack of community care or attention to the facilities and infrastructure that has been built. These constraints are relative obstacles, but the village government always tries to overcome these obstacles so that the development program that has been implemented can later be maintained and used as best as possible by the community.